The Study of Covid-19 Impact on Four Season Resort, Langkawi Malaysia - Teoh, Kok Ban; Pérez, Camilo; Shaikh, Sanowar; Muthraj, Roshni Guru; Fen, Khow Pei; Xuan, Lim Ee (AIBPM Publisher, 2023)
The Covid 19 outbreak is spreading across the globe, affecting the health of thousands people and creating shocks in almost all industries due to restrictions and policies to work from home (self-quarantine) to break the chain of virus spread. The consequences of steps taken by the countries of the world to curb the pandemic have a huge impact on the global economy. Four Season Resort Langkawi Malaysia is an international luxury hotel and resort. However, the Covid 19 pandemic has had a negative impact on the sustainability of this industry. Therefore, this study aims to understand the performance and investigate the problem faced by Four Season Resort Langkawi Malaysia.